Iterative space-frequency equalization techniques for LTE - Loução, Luís Pedro Santos (2014)
Mobile communications had a huge leap on its evolution in the last decade due to the constant increase of the user requirements. The Long Term Evolution is the new technology developed to give proper answer to the needs of a growing mobile communications community, offering much higher data rates, better spectral efficiency and lower latency when compared to previous technologies, along with scalable bandwidth, interoperability and easy roaming. All these advantages are possible due to the implementation of new network architectures like the E-UTRAN access network and the EPC core network, the use of MIMO systems, and new multiple access schemes: OFDMA for downlink and SC-FDMA for uplink. This thesis focuses on the uplink communication of this technology with SC-FDMA, specifically on the use of Iterative Block Decision Feedback Equalizers (IB-DFE) where both the feedback and the feedforward equalizer matrices are applied on the frequency domain. Two IB-DFE schemes were implemented using both Parallel Interference Cancellation (PIC) and Serial Interference Cancellation (SIC) based processing. We considered the uplink scenario where some users share the same physical channel to transmit its own information to the Base Station (BS). Also, we consider that the BS is equipped with multiple antennas and the user terminals (UT) with a single antenna. The aim of the studied iterative schemes is to efficiently remove both the multi-user and inter-carrier interferences, while allowing a close-to-optimum space-diversity gain. The results obtained showed that both PIC and SIC implementations presented better performance than the conventional used linear multi-user sub optimal equalizers ZF and MMSE. Both solutions efficiently eliminate the multi-user interference, although the SIC based scheme slightly outperforms the PIC approach, with a performance close to the one achieved by the Matched Filter Bound (MFB).